2010
DOI: 10.1103/physreve.81.041111
|View full text |Cite
|
Sign up to set email alerts
|

Equilibriumlike invaded cluster algorithm: Critical exponents and dynamical properties

Abstract: We present a detailed study of the Equilibriumlike invaded cluster algorithm (EIC), recently proposed as an extension of the invaded cluster (IC) algorithm, designed to drive the system to criticality while still preserving the equilibrium ensemble. We perform extensive simulations on two special cases of the Potts model and examine the precision of critical exponents by including the leading corrections. We show that both thermal and magnetic critical exponents can be obtained with high accuracy compared to t… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
7
0

Year Published

2012
2012
2014
2014

Publication Types

Select...
3

Relationship

2
1

Authors

Journals

citations
Cited by 3 publications
(7 citation statements)
references
References 32 publications
0
7
0
Order By: Relevance
“…In our previous works [29,34], we have shown that introducing auxiliary parameters, which constrain the resulting distribution of bond probability p to the width narrower than L − d 2 , reestablishes the sampling of the canonical ensemble. Such a modified algorithm thus produces the equilibrium configurations at the quasicritical point of the finite system.…”
Section: A Eic Approachmentioning
confidence: 98%
See 3 more Smart Citations
“…In our previous works [29,34], we have shown that introducing auxiliary parameters, which constrain the resulting distribution of bond probability p to the width narrower than L − d 2 , reestablishes the sampling of the canonical ensemble. Such a modified algorithm thus produces the equilibrium configurations at the quasicritical point of the finite system.…”
Section: A Eic Approachmentioning
confidence: 98%
“…We have chosen the set of auxiliary parameters of the EIC algorithm [29,34] to be v = 1 10 L −1.1 and N a = 1000. The values of [p 2 α − p 2 α ] (Fig.…”
Section: A Details Of the Simulationmentioning
confidence: 99%
See 2 more Smart Citations
“…Recent efforts on the theoretical and numerical studies can be found for example in Refs. [1][2][3][4][5][6][7][8][9][10][11][12][13][14][15][16]. It has been rigorously proven that an infinitesimal amount of quenched disorder coupled to the energy density will turn a first-order transition to a continuous one when the spatial dimension d 2 [17,18].…”
mentioning
confidence: 99%